Microsite-based career guidance to enhance career exploration of junior high school student: a pilot study - Muryono, Sigit (Universitas Negeri Padang, 2022)
Life and career skills are one life skills that should developed by students in order to prepare themselves for the future. The efforts to develop career skills for students through guidance and counseling services are relevant to conducted by educational institutions. This study aims to describe the feasibility and effectiveness of microsite-based school career guidance programs to enhance career exploration of junior high school students. The experiment with one-group pretestand posttest design wasconducted by involving 60 junior high school students (age 13 – 15) were selected by intact group by class. The career explorations cale isused to measure student’s career exploration before and after students following the career guidance program through microsite. The student’s perception questionnaire was used to evaluate student responses about the feasibility and acceptability of the microsite-based career guidance. Results of this study shows (1) microsite-based career guidance has good acceptability based on student responses that states the media was easy to access and useful, and (2) microsite-based career guidance is effective for enhancing student’s career exploration. The results of this study have implications for the use of ICT’s in developing career guidance and counseling media.